Материалы к изучению пищи амфибий в районе среднего течения Северского Донца - Медведев, С.И. (Вестник зоологии, 1974)
The article deals with the results of analysis of food from the stomaches of amphibians Rana esculenta L., R. ridibunda Р а 1 1., R. terrestris Ап г., Виго viridis L а и г., В. bufo L., Pelobates fuscus 1.4 а и т., Bornbina bombina L. collected in summer 1955—1958 in the valley of the Seversky Donets river at the Zmievkskian biostation of the kharkov University. The species composition of animals, found in the amphibians stomaches, is determined; the peculiarities of their ecology (connection with the definite biocenoses and synusias, behaviour, biological peculiarities, manner of life and diurnal activity) аге тепtioned. The economic value of the eated species is also dealt with.